2001
DOI: 10.1038/sj.onc.1204208
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the focal adhesion kinase/Src signal transduction pathway correlate with increased migratory capacity of prostate carcinoma cells

Abstract: Focal adhesion kinase (FAK) has been implicated in the regulation of cell migration. In addition, FAK expression is increased in a number of highly metastatic tumor cell lines. Therefore, we investigated the role of FAK in regulating migration of prostate carcinoma cell lines with increasing metastatic potential. We show that highly tumorigenic PC3 and DU145 cells exhibit intrinsic migratory capacity, while poorly tumorigenic LNCaP cells require a stimulus to migrate. Increased metastatic potential of PC3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
148
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(159 citation statements)
references
References 56 publications
(78 reference statements)
8
148
0
2
Order By: Relevance
“…These observations support the results of our study. Slack et al demonstrated that an increase in FAK expression, coupled with tyrosine phosphorylation of FAK on tyrosine 861, may contribute to the increased cell motility of highly tumorigenic prostate cancer cells (Slack et al, 2001). Overexpression of FAK may alter the motility of ESCC cells, and as a result of this high motility, FAK protein might be overexpressed in those patients with more invasive and metastatic ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…These observations support the results of our study. Slack et al demonstrated that an increase in FAK expression, coupled with tyrosine phosphorylation of FAK on tyrosine 861, may contribute to the increased cell motility of highly tumorigenic prostate cancer cells (Slack et al, 2001). Overexpression of FAK may alter the motility of ESCC cells, and as a result of this high motility, FAK protein might be overexpressed in those patients with more invasive and metastatic ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Although activation of Src has been positively correlated with both cell proliferation and invasiveness of several prostate cancer cell lines, 17,18,21 no data are currently available on the activation of Src in primary prostate tumors. Herein we have investigated activation of Src by assaying the level of tyrosine phosphorylation of the kinase, which is directly correlated to its activity status.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Furthermore, Sam68 is highly expressed in prostate epithelial cells and the involvement of this protein in RNA metabolism during normal growth and neoplastic transformation of prostatic cells has recently been hypothesized. 19 Herein we undertook an analysis of prostate cancer cell lines and primary prostatic tumors for the presence of human tr-Kit.…”
mentioning
confidence: 99%
“…Whereas high levels of FRNK can promote cell apoptosis (Xu et al, 2000;Golubovskaya et al, 2002), FRNK expression can also reduce tumor growth by promoting tumor dormancy and by inhibiting cell proliferation (Aguirre Ghiso, 2002;van Nimwegen et al, 2005). Low levels of FRNK expression have revealed the importance of FAK activity in promoting tumor cell migration (Slack et al, 2001) and in generating an invasive cell phenotype (Hauck et al, 2001(Hauck et al, , 2002bHsia et al, 2003;.…”
Section: Introductionmentioning
confidence: 99%